As diferenças na estética vocal do canto lírico e do canto popular no canto coral - Ravizzoni, Daniela Carraro (My University, 2024)
This research is a study on the differences in the practice of singing teachers when developing the vocal aesthetics of works of lyrical and popular singing within the scope of choral singing. After an introductory explanation about the voice production, definitions of choral singing and the characteristics that involve vocal aesthetics are presented, in addition to the following categories that encompass it: timbre, vocal registration, homogeneity and balance, resonance. The research approach was qualitative through an exploratory study. The method was the study of multiple cases that counted on the report of three professionals with more than ten years of experience in choral preparation. Semi-structured interviews were conducted to collect data on the experience of singing teachers in vocal preparation. From the analysis of the interviewees' discourse, it was possible to conclude that the vocal technique for the development or improvement of the vocal quality of the singers is usually performed thinking about the construction of the aesthetics of the repertoire in question and that the most susceptible aspects are the adjustments supra-glottis, the shape of the vowels, the articulation and the work with different types of timbres. [resumo fornecido pelo autor]
Este trabalho é um estudo sobre as diferenças na prática de professores de canto ao desenvolverem a estética vocal de obras do canto lírico e popular no âmbito do canto coral. Após um esclarecimento introdutório sobre a produção da voz, são apresentadas definições de canto coral e das características que envolvem a estética vocal, além das seguintes categorias que a englobam: timbre, registração vocal, homogeneidade e equilíbrio, ressonância. A abordagem da pesquisa foi qualitativa por meio de um estudo exploratório. O método foi o estudo de casos múltiplos que contou com o relato de três profissionais com mais de dez anos de atuação na preparação coral. Foram realizadas entrevistas semiestruturadas para a coleta de dados sobre a experiência dos professores de canto na preparação vocal. A partir da análise do discurso dos entrevistados, foi possível concluir que a técnica vocal para o desenvolvimento ou aprimoramento da qualidade vocal dos cantores é normalmente realizada pensando na construção da estética do repertório em questão e, que os aspectos mais passíveis de modificação são os ajustes supraglóticos, o formato das vogais, a articulação e o trabalho com diferentes tipos de timbres. [resumo fornecido pelo autor]
Keywords: Música; Voz - Educação; Canto coral; Professores de canto; Música popular; Ópera; Canto - Instrução e estudo